ECONOMIC CONVERGENCE ACROSS DISTRICTS/CITIES IN SOUTH EAST SULAWESI PROVINCE : ROLE AND CONTRIBUTION OF MINING SECTOR - LEDY ALAM (NIM : 22110027), APERTA
The economic convergence across districts/cities in Southeast Sulawesi Province is a necessity in the development activities. Patterns of economic convergence across districts/cities in Southeast Sulawesi Province should be used as guidance to governments to develop an equitable economic growth. It is necessary to reduce the disparities between district's/city's economic growth through developing priority sectors. The priority could be identified using analysis of Location Quotients (LQ). Mining sector, with value of LQ > 1 is only found in Buton District and Kolaka District. Nevertheless at the provincial level, the LQ of mining sector is less than one. The econometric model is applied to obtained a detailed analysis of the role of mining sector to the regional economic development. Through regression equations with four variables, it is obvious that the mining sector as a dependent variable influence only the growth of the Gross Regional Domestic Product (GRDP) in Kolaka District and Buton District. Analysis of input-output tables (I-O) become an important step to determine the linkages between the upstream and downstream sectors as well as calculate the values of multipliers of each sector. The values of upstream and downstream linkages which is greater than one is found in the manufacturing sector, while for the mining sector linkages the upstream and downstream linkages value less than one. Multiplier value on surplus, investment, income, and employment shows a great value in the manufacturing sector. The economic indicators obtain form this study become a factor in the development of Southeast Sulawesi province in the framework of meet development objectives in the long-term development plans and medium term.